THE IMPACT OF THE WEATHER CONDITIONS ON THE QUALITY OF BIRCH VENEER LOGS DURING WINTER HARVESTING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The external characteristics of a tree give the only clue to the quality of veneer log obtained in harvesting. When the tree is bucked into veneer logs, the cross sections at the butt and top ends of these assortments may provide additional indicators of the quality. Thus, it becomes important to study the abnormalities that can be seen on the end surface of the veneer logs such as heart shakes, and to correlate the occurrence of these imperfections with the quality of veneer that is produced from the veneer log.Therefore, the purpose of this study was to: (1) identify and measure heart shakes length, width and depth in wood in all investigated veneer logs diameter groups: 180-249mm; 250-299mm, 300<mm in the period of storage, (2) identify the factors that could initiate heart shakes in veneer logs in the period of storage (number of storage days, weather temperature, moon phases, relative humidity) in all diameter ranges, (3) by analysing the results to work out the recommendations to improve the forest management in forest stands when veneer logs are manufactured.